Premature Termination Codon of 1Dy12 Gene Improves Cookie Quality in Ningmai9 Wheat - Liu, Guangxiao; Gao, Yujiao; Wang, Huadun; Wang, Yonggang; Chen, Jianmin; Zhang, Pingping; Ma, Hongxiang (Frontiers in Plant Science, 2022)
The middle to lower reaches of Yangtze River is the largest area for soft wheat production in China. Lack of germplasm with desirable quality for end-use products is a barrier in soft wheat breeding. Ningmai 9 was the major variety of soft wheat planted in this area. To create the germplasm with better quality and yield potential than those in Ningmai 9, mutants of HMW-GSs in Ningmai 9 induced by ethylmethanesulfonate (EMS) were obtained. SDS-PAGE showed that two mutants md10 and md11 were HMW-GS 1Dy deletions. DNA sequencing confirmed that one mutation was caused by a C/T substitution, resulting in the change of CAA encoding glutamine into the stop code TAA, and another mutation is due to a G/A substitution in central repetitive domain of the coding region, causing the tryptophan encoding TGG to become the stop codon TGA. Premature stop coding of 1Dy12 gene affected the expression of 1Dy12 and kept the mRNA at a lower transcription level during kernel development stage in comparing with wild type. HMW-GS 1Dy12 deletion mutants decreased the content of HMW-GSs and glutenin macropolymers, mixograph envelope peak time and TIMEX width, water solvent retention capacity (WSRC) and lactic acid solvent retention capacity (LASRC). In the HMW-GS 1Dy12 deletion lines, sugar-snap cookie diameter was 8.70-8.74 cm, significantly larger than that in the wild type of 8.0 cm. There was no significant difference in spike number, kernel number, thousand kernel weight and yield between deletion lines and wild type. Overall, the study indicated that HMW-GS gene knockout can be used to improve soft wheat quality and deletion mutants of HMW-GS 1Dy12 weakened gluten strength and improved sugar snap cookie processing quality without yield penalty in Ningmai 9 wheat.